IMPROVING STUDENTS’ SCIENTIFIC WRITING ABILITY THROUGH COLLABORATIVE LEARNING - Hasanuddin, Dede; Emzir; Akhadia, Sabarti (Prosiding Seminar Nasional Berseri, 2020)
Scientific writing is a way for someone to put the concept of thinking in written form so that other people can understand what is being thought. The purpose of this study is to improve the students’ scientific writing through Collaborative Learning by utilizing blended learning. The method used here is an action research using collaborative learning. It is applied for students’ learning in writing scientific paper. The students are expected to have logical thinking aspects, data objectivity, vocabulary mastery, use of Enhanced Spelling (EYD), use of effective sentences, and paragraph development. The result showed that collaborative learning can improve students’ ability to write scientific articles since in collaborative learning students are very active, motivated and always intrigued by their hearts and minds to solve problems faced in group, and they can also work competitively, and motivate other students to achieve the maximum learning outcomes.